1992
DOI: 10.1007/bf01783485
|View full text |Cite
|
Sign up to set email alerts
|

Selenium deficiency in Yugoslavia and possible effects on health

Abstract: New data on Se-deficiency in Yugoslavia are presented. The results include Se contents of soils, cereal crops and garlic grown in the investigated soils, and human serum and scalp hair from several towns and regions in this country. All data indicate a serious Se-deficiency. Analyses of human tissues show a very low Se-status of the Yugoslav population. In some regions, Se contents of garlic, grains and human serum and hair are approaching those in the low-selenium zone in China. It is assumed that the very lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 6 publications
2
18
0
1
Order By: Relevance
“…Silica and the following elements have been assayed in water and/or soil of endemic regions : lead, uranium, copper, cobalt, zinc, manganese, arsenic, titanium, barium, aluminium, chromium, strontium, cadmium, bismuth, molybdenum, nickel, tungsten, antimony and tin (Kussitasseva et al 1960, Nikiforov 1960, Anguelieva and Mladenova 1972, Pasare et al 1975, Markovic et al 1976, Nichifor et al 1985, Markovic 1988, 1990, Radovanovic 1989, Wedeen 1991, Maksimovic et al 1992, Bobinac 1996, Maksimovic and Djujic 1997. In most cases, the concentrations were below the permissible levels or below the detection limits of the analytical methods used.…”
Section: Metals Other Elements and Mineralsmentioning
confidence: 99%
See 1 more Smart Citation
“…Silica and the following elements have been assayed in water and/or soil of endemic regions : lead, uranium, copper, cobalt, zinc, manganese, arsenic, titanium, barium, aluminium, chromium, strontium, cadmium, bismuth, molybdenum, nickel, tungsten, antimony and tin (Kussitasseva et al 1960, Nikiforov 1960, Anguelieva and Mladenova 1972, Pasare et al 1975, Markovic et al 1976, Nichifor et al 1985, Markovic 1988, 1990, Radovanovic 1989, Wedeen 1991, Maksimovic et al 1992, Bobinac 1996, Maksimovic and Djujic 1997. In most cases, the concentrations were below the permissible levels or below the detection limits of the analytical methods used.…”
Section: Metals Other Elements and Mineralsmentioning
confidence: 99%
“…According to Radovanovic (1989),`an excess of any heavy metal or radioactive substance as a cause of BEN is very unlikely indeed; however, a de®ciency of a bioessential element could not be ruled out. ' Maksimovic et al (1992) and Maksimovic and Djujic (1997) subsequently postulated that the diseases might be linked to selenium de®ciency. In his review, Bobinac (1996) concluded that`There were not enough solid results to justify determined viewpoints and, consequently, no intense confrontation, with the exception of our opposition to the then marked opinion on lead intoxication as a causative agent.'…”
Section: Metals Other Elements and Mineralsmentioning
confidence: 99%
“…Our data compare favorably with data reported in Hungary where Se content in wheat ranged from 5 to 235 µg/kg (Alfthan et al 1992). Low Se values have been reported from Yugoslavia (Maksimovic et al 1992) in the range of 3.6 to 65.5 µg/kg with an average of 18 µg/kg. The most extreme values for the Se content of wheat were reported from Sweden, the Federal Republic of Germany, Scotland and Norway and ranged from 9 to 34 µg/kg (Kumpulainen 1993) In seleniferous areas of Venezuela, Se content in wheat was found to be in the range of 25 to 250 µg/L (Bratter et al 1991).…”
Section: Methodsmentioning
confidence: 99%
“…Around the world, there are regions that are so poor in Se that overt deficiency syndromes are endemic (Tapiero et al, 2003). Se deficiency is also of concern in Europe ( Mayland et al, 1989;Fordyce, 2005;Rayman, 2012), including Western Balkans (Maksimovic et al, 1992;Popijac & Prpic-Majic, 2002;Manojlovic & Singh, 2012).…”
Section: Introductionmentioning
confidence: 97%